Clinical Encounters in Sexuality: Psychoanalytic Practice and Queer Theory - Watson, Eve; Giffney, Noreen (Book collections on Project MUSE., 2020)
Clinical Encounters in Sexuality makes an intervention into the fields of clinical psychoanalysis and sexuality studies, in an effort to think about a range of issues relating to sexuality from a clinical psychoanalytic perspective. The editors have chosen queer theory as an interlocutor for the clinical contributors, because it is at the forefront of theoretical considerations of sexuality, as well as being both reliant upon and suspicious of psychoanalysis as a clinical practice and discourse. The book brings together a number of psychoanalytic schools of thought and clinical approaches, which are sometimes at odds with one another and thus tend not to engage in dialogue about divisive theoretical concepts and matters of clinical technique. The volume also stages, for the first time, a sustained clinical psychoanalytic engagement with queer theory. The central questions we present to readers to think about are: What are the discourses of sexuality underpinning psychoanalysis, and how do they impact on clinical practice? In what ways does sexuality get played out for, and between, the psychoanalytic practitioner and the patient? How do social, cultural and historical attitudes towards sexuality impact on the transference and countertransference, consciously and unconsciously? Why is sexuality so prone to reification?